The association of COVID-19 incidence with sport and face mask use in United States high school athletes - Watson, A. M.; Haraldsdottir, K.; Biese, K. M.; Goodavish, L.; Stevens, B.; McGuine, T. A. (Journal of Athletic Training, 2023)
Context The relationships among different sports, face mask use, and COVID-19 risk among high school athletes remain unknown.